The needs and Preferences of Graduate Teachers in Relation to their Professional Development - (:unkn) unknown (University of Jaffna, 2014)
The aim of this study was to explore the professional development needs and preferences of Graduate teachers. This study was conducted in Jaffna District. Target population of this study consisted of Graduate teachers completed their Post Graduate Diploma in Education in 2012/2013 academic year either at Open University of SriLanka or at University of Jaffna. Sample consisted 30 student teachers from each institution. Survey research design was used for this study, in which data were collected through a self developed survey questionnaire to teachers and analysed in percentages. A total of 51 student teachers responded for the survey. The findings indicated that 16 areas of professional development such as command of subject matter knowledge, use of modern t echnology, production of teaching materials etc were perceived as very urgent needs by the teachers. The results further showed that some of these needs such as skills to use modern technology, skills to manage student discipline and behaviour problems, skills in conflict resolution were not satisfied by the professional development programmes for Graduate teachers. Institutions involved in teachers’ professional development can also use the findings of this study to improve the quality of their programmes.
Keywords: Graduate teachers; Needs and preferences; Professional development.